PERILAKU HARIAN MACACA HECKI DIHUTAN AREA DESA MAKARTI JAYA POHUWATO GORONTALO - Mustamin Ibrahim; Chairunnisah J. Lamangantjo; Regina Eka Cahyani Mooduto (Universitas Lancang Kuning, 2023)
Macaca hecki is an animal endemic to Sulawesi where this primate is a protected animal due to its increasing extinction. The behavior of Macaca hecki is very unique by moving simultaneously, the behavior carried out is argonistic behavior carried out simultaneously with eating behavior, eating behavior carried out simultaneously with resting behavior, primates have group behavior with various interactions, one of which is moving, eating, socializing and making sounds, the problem formulation of this research is how the daily behavior of Macaca hecki in the forest area of Makarti Jaya Pohuato village, Gorontalo., with the aim of knowing daily behavior. Macaca hecki in the forest area of Makarti Jaya Pohuwato Gororntalo village, the behavior of individual Macaca hecki that dominates the most or the highest daily activity of Macaca hecki in the forest of Makarti Jaya village is movement behavior (49.03%), while for the lowest daily activity category Macaca hecki individuals carry out in the forest Makarti Jaya village is grooming behavior as much as (2.83%), Macaca hecki is a diurnal animal, namely an animal that carries out its activities during the day, either looking for food or while moving. Every day Macaca hecki carries out moving activities to look for food or do other activities, Resting activities are carried out to carry out eating and grooming behavior. Macaca hecki is a diurnal animal that has an aggressive nature towards disturbances.